Perceptions of the Zika Virus, Contraceptive Access, and Motivation to Participate in the Zika Contraception Access Network Program: Qualitative Analysis of Focusgroup Discussions with Puerto Rican Women - Romero, Lisa; Acosta-Pérez, Edna; Bednar, Hailey; Hurst, Stacey; Zapata, Lauren B.; Vega-Torres, Samaris; Powell, Rachel; Lathrop, Eva (Puerto Rico Health Sciences Journal, 2024)
Objective: During the 2016-2017 Zika virus outbreak in Puerto Rico, the Zika Contraception Access Network (Z-CAN) provided client-centered contraceptive counseling and access to the full range of reversible contraceptive methods at no cost to prevent unintended pregnancies and thereby to reduce Zika-related birth outcomes. Methods: To understand how Puerto Rican women’s perceptions of the Zika virus affected contraceptive decisions and assess how they heard about the Z-CAN program and what influenced their participation, or lack thereof, 24 focus-group discussions were conducted among women of reproductive age who did and did not participate in Z-CAN. Results: Women who participated in the discussions often had heard about Z-CAN from their physician or friends; non-participants had heard about Z-CAN from Facebook or friends. Women expressed satisfaction on finding a Z-CAN clinic and valued the same-day provision of contraceptives. When a preferred contraceptive method or a first appointment was not readily available, women reconsidered accessing the program. Women’s perceptions and trust of reproductive healthcare providers, their engagement in social networks, and their ability to choose a contraceptive method that best meets their needs can influence participation in contraception-access programs. Conclusions: Focus groups can be used to understand women’s knowledge of the Zika virus, barriers and facilitators to contraception access, and motivations for participation in the Z-CAN program.